Sustaining Screening, Brief Intervention and Referral to Treatment (SBIRT) services in health‐care settings. (February 2017) - Singh, Manu; Gmyrek, Amanda; Hernandez, Amy; Damon, Donna; Hayashi, Susan; Del Boca, Frances K.; Babor, Thomas F.; Bray, Jeremy W.
Abstract: Aims: To assess the sustainability of Screening, Brief Intervention and Referral to Treatment (SBIRT) services after cessation of initial start‐up funding. Design: Descriptive study with quantitative and qualitative data collected from 34 staff participants from six grantees (comprising 103 sites) funded previously through a large, federally supported SBIRT program. Setting: Primary care out‐patient clinics and hospitals in the United States. Participants: Thirty‐four grantee‐related staff members, including administrators, evaluators, key stakeholders and SBIRT service providers from six grantees. Measurements: Changes to levels and types of service delivery activities after federal funding stopped, alternative sources of funding and obstacles to delivery of services. Findings: Of the 103 original sites in the six SBIRT grantee programs, 69 sites continued providing services in some capacity (same as before, reduced, modified or expanded). Most of the 69 sites (67%) adapted and redesigned the delivery of SBIRT services post‐initial grant funding. In addition, new sites were added after grant funding ended, bringing the total number of sites to 88. Analysis of participant responses identified four primary factors that influenced SBIRT sustainability: presence of champions, funding availability, systemic change and SBIRT practitioner characteristics. Conclusions: Almost 70% of the Screening, Brief Intervention and Referral to Treatment (SBIRT) services in the United States funded initially through a federal program were able to sustain operations after federal funding ceased and some expanded SBIRT services beyond the original sites. The key factors related to sustainability were securing new funding, having champions, adapting and making system changes and managing program staffing challenges.